Supplementary reading materials for â€œWhen English rings the bellâ€ - Muhammad Mustangin; Yuyun Yulia (Journal of English Language and Pedagogy, 2019)
This study is aimed at developing supplementary reading materials based on â€œWhen English Rings the Bellâ€ and describing the effectiveness of the developing supplementary reading. This research belongs to Educational Research and Development (R&D) which are simplified into six steps. They are (1) data collection by document analysis, questionnaire, interview, product testing, as well as expertsâ€™ judgment, (2) constructing the course grid (Nation & Macalister, 2010), (3) draft revision by experts, (4) developing product to the preliminary outcome, (5) evaluation and revision of the product, and (6) final product. The findings show that studentsâ€™ necessity to learn English is to be able to comprehend English (82.35%) and to increase vocabulary (50%) with interesting text. However, in other hand, their lack in vocabulary (52.94%) and the activities are too various (44%). The targeted materials are Getting My Idea for the descriptive text, My Pleasant Experience for the recount text, and Tell Me Your Story for the narrative text. Each unit consists of introduction, learning procedure, reinforcement, and wise word. Accordingly, the effectiveness of the product helps students to achieve the targeted competences. The students were actively participating in answering the task. The supplementary reading could help students to achieve studentsâ€™ need and to improve their participation in reading skill. Furthermore, the reading materials as the product of this study providing additional learning resources.